Cannabis use during the early COVID-19 pandemic: Use patterns, predictors, and subjective experiences - Mielau, Juliane; Reiche, Simon; Moon, Daa Un; Groß, Elisa; Gutwinski, Stefan; Betzler, Felix; Romanello, Amy; Masah, Dario Jalilzadeh; Scicchitano, Matteo; Marek, Roman; Brandt, Lasse; Evens, Ricarda; et al. (Frontiers in Psychiatry, 2023)
Even in the early stages, global crises such as the COVID-19 pandemic lead to serious dislocations of social life, secondary adjustment reactions to external restrictions and individual concerns. Coping mechanisms may also include dysfunctional strategies like an increase of drug use. Considering the wide-spread use of cannabis, the aim of this study was to elucidate the interplay of social restrictions, psychopathology, concerns related to the pandemic in addition to the users’ experiences, motivations and consumption quantities during the early COVID-19 pandemic. It was presumed that cannabis intake would increase during the early phase of the crisis and that consumption quantities would be related to corona-related restrictions, concerns as well as subjective substance effects and psychopathology. As part of an international, cross-sectional, internet-based survey (N = 5049) available in 5 languages, consumption quantities and patterns of cannabis use in the early phase of the pandemic from April to August 2020 were examined. Participants retrospectively rated restrictions and concerns related to the pandemic, motives of cannabis use prior to and during one month the pandemic, and subjective consumption effects. Cannabis use behavior showed no significant differences when consumption quantities prior and during one month after the COVID-19 outbreak were compared. Higher quantities of cannabis intake prior and during one month of the pandemic as well as more corona-related concern were associated with an increased perception of positive effects of cannabis during the pandemic. Predictors of its use during one month of pandemic were higher pre-pandemic consumption quantity, older age, quarantinization, a lesser degree of being affected by negative effects of the pandemic and a stronger subjective experience of Corona-related positive effects of cannabis. Comparisons of the motives for cannabis intake in the pre-pandemic versus the pandemic period showed that all rationales for consumption were reported less frequently, except boredom. Frequencies of cannabis intake remained relatively stable in the early pandemic phase. Risk factors for increased use seem related to habitual consumption patterns that become more prominent under quarantinization. The use of cannabis as a dysfunctional coping strategy might not be amenable via self-report and should therefore receive special attention in clinical contexts.